Responsibility to Protect (R2P) and the Syrian Refugee Crisis: A missed opportunity? - Duarte,Francisco de Abreu (2016)
The paper debates the concept of Responsibility to Protect (R2P) and its applicability to the recent humanitarian Syrian crisis. By providing an insight on the conflict, it applies the general requisites of the doctrine to the situation at hand, providing different approaches to it. The general view of R2P as an emerging norm of customary international law is then challenged in the light of the conflict, assessing the reasons why it was considered not applicable under the mass atrocities perpetrated in Syria since 2011, asserting that there is nothing normatively new about the doctrine. The paper suggests instead that R2P's strongest argument is on its didactic and conceptual simplicity, which can be used to provide a better enforcement of already existing norms, proving its applicability as such.